“I really like to study english”: positive attitudes toward learning the english language - Anjos, Flávius Almeida dos (Universidade Estadual Paulista, 2021)
This paper was elaborated under the aegis of Applied Linguistics. The central theme are the positive attitudes of English learners. In the core of this reflection some factors emerge directly related with attitudes, such as motivations and orientation to learn a foreign language. The objective of this paper is to discuss how the attitudes are originated, highlighting the elaboration of a continuum of positive attitudes, to better understand them. Therefore, some data are presented, an ethnographic research, generated from an interview, which was conducted with 91 undergraduate students, from the Recôncavo of Bahia Federal University, which pointed to the occurrence of instrumental and integrative orientations and of motivation. The relevance of this work rests on the fact that these data may support teachers of English to have a more accurate understanding of their attitudes.